Effect Of Theraband Exercise Therapy On Pain Reduction In Osteoarthritis Patients At Puskesmas Citra Medika Lubuklinggau City - Hayati, Rima; Novitasari, Deltari; Harison, Nunu (Universitas Dehasen Bengkulu, 2023)
Theraband exercise, a type of elastic resistance exercise that allows many different movements to increase muscle strength, joint mobility, function and reduce joint pain in osteoarthritis sufferers. The research problem is the increase in patients experiencing pain in osteoarthritis. The purpose of this study was to determine the effect of theraband exercise therapy on reducing pain in osteoarthritis patients at the Citra Medika Health Center, Lubuklinggau City. This study is a quantitative method with a pre and post test design. In this study, the treatment group will receive theraband exercise therapy. The total population studied was 253 people, and only 10 samples were taken. The Wilcoxon test (non-parametric) was used to analyze primary and secondary data. The results of this study were the average value of pain reduction before using theraband exercise therapy in osteoarthritis patients, namely 5.10. The average value of pain reduction after using theraband exercise therapy in osteoarthritis patients was 2.20. There is an effect of theraband exercise therapy on reducing pain in osteoarthritis patients at the Citra Medika Health Center, Lubuklinggau City with a p value of 0.004.For the Citra Medika Health Center, Lubuklinggau City, they can include theraband exercise therapy in routine program activities at the Citra Medika Health Center, Lubuklinggau City and carry out theraband exercise therapy as a nursing intervention to reduce pain in osteoarthritis patients.